Caribbean Report 19-05-1999 - The British Broadcasting Corporation; Greaves, Keith Stone (anchor, correspondent); Lewis, Lincoln (interviewee); Smith, Colin (correspondent); Hughes, Hubert (interviewee); Banks, Victor (interviewee); O'Neal, Ralph Telford (interviewee); Burns-Piper, Angela (correspondent); Jarvis, Mike (correspondent); Morley, Elliot (interviewee); Perreira, Joseph 'Reds' (interviewee) (The British Broadcasting Corporation, 1999)
1. Headlines with anchor Keith Stone Greaves (00: 27) 2. In Guyana the relationship between the government and trade unions have worsened following police shooting on demonstrators. Trade unionists have called on demonstrators to go on a seventy two hour country wide strike. Head of the Trade Union Congress Lincoln Lewis said Union members have cancelled their talks with the government until shootings by police have been investigated and an independent enquiry conducted. Colin Smith and Keith Stone Greaves report (00:28 – 04:10) 3. The Anguillan government is heading into conflict with two members from the coalition Anguilla Democratic Party threatening to resign. Prime Minister Hubert Hughes and Finance Minister Victor Banks comment on the political impasse (04:11 – 07: 51) 4. Ralph Telford O'Neal is sworn in as Chief Minister in the British Virgin Islands following his party narrow win in the just concluded elections. The Chief Minister discusses the political campaign and election results. Angela Burns- Piper reports on the ministerial portfolios (07: 52 – 09: 42) 5. In Dutch Sint Maarten the deadline has passed for the federal government to reduce the gasoline excise tax as requested by the local administration. The oil companies requested an eight cents per liter increase and threatens to close petrol stations. Mike Jarvis reports (09: 43 - 11:37) 6. British Fisheries Minister Elliot Morley reviews the international approach to the protection and management of whales at an International Whaling Commission in Grenada. Keith Stone Greaves reports (11:38 – 13: 18) 7. In the World Cup Series in England, Zimbabwe scored an upset win over India winning by three runs. South African won against defending champion Sri Lanka. Cricket commentator Reds Perreira analyses the matches ( 13:19 – 15: 26)